Electrical Characteristics and Annealing Effect on Al/n-GaSb Schottky Diode Doped Using DMTe - Ari Handono Ramelan; Harjana Harjana; Pepen Arifin; Ewa Goldys (Institut Teknologi Bandung, 2010)
The electrical properties of Al/n-GaSb Schottky diodes, doped with 1.4 Ã 1018 cmâ3 (tellurium) were examined.Â C-V (capacitance-voltage) measurements at 300 K show barrier heights of 0.63 eV, compared to 0.59 eV determined from room temperature I-V (current-voltage)Â measurements. The voltage and frequency dependence on the capacitance is due to the ideality factor of the Schottky barrier and due to a high series resistance.Â At low frequency the measured capacitance is dominated by the depletion capacitance of the Al/n-GaSb Schottky diode which is bias-dependent and frequency-dependent. The diode shows a strong temperature dependence of ideality factor from approximately 3.6 at room temperature to as high as 6.7 at 140 K.Â There may be a small portion of the device nonideality attributable to generation-recombination currents due to deep levels in GaSb. The barrier height decreased from 0.57 eV to 0.35 eV for the sample annealed at 300oC for 1 minute.